Media Pembelajaran Permainan Rubik Dalam Meningkatkan Pemahaman Santri Tentang Bangun Ruang - Siti Rahmah Nurshiami; Jajang; Acep Taryana (CV. Multi Kreasi Media, 2024)
One of the competencies that students must have in learning mathematics is the spatial ability to understand the material of spatial figures. Students' spatial skills can be trained and developed by using teaching aids. This community service activity was carried out to improve the understanding of male students of SMPIT Harapan Bunda Purwokerto about the material of spatial figures. Rubik's games are used as learning media/teaching tools to understand the concept of spatial figures and their properties. The theoretical and practical knowledge transfer methods were carried out in this community service activity. The activity began by giving a pre-test to see the students' understanding of the material of spatial figures. The results of the pre-test showed that 65.21% of students could answer each point correctly, while the results of the post-test showed an increase in students' understanding of 85.42%. Based on these data, it can be seen that the use of Rubik's learning media provided during the activity increased the students' understanding of mathematical concepts for the topic of spatial figures by 20.21%.